APPLICATION OF EULER DECONVOLUTION AND UPWARD CONTINUATION METHODS USING GEOMAGNETIC DATA TO IDENTIFY THE STRUCTURE AND DISTRIBUTION OF MINERALS IN THE OLAT TANAH MERAH AREA, SUMBAWA REGENCY, WEST NUSA TENGGARA - Nur Fara Diba Sillehu, Sitti
The Olat Tanah Merah area, Teluk Santong Village, Sumbawa Regency has the potential for the distribution of sulfide metal mineral deposits such as copper, gold and silver. To find out the potential distribution of metal minerals, a geophysical study was conducted using geomagnetic methods. This study uses total magnetic anomaly data in 2014 obtained from PSDG and other supporting data such as topographic, geological and geochemical data. In this study, the reduce to pole (RTP) process was carried out. Furthermore, regional and residual anomalies were separated using the upward continuation separation method with a lifting height of 250 m and a Butterworth filter. The Euler Deconvolution method was also used to determine the location and depth of the geological structure of the study area. The results obtained show that the RTP process changes the dipole anomaly response to monopole. Based on the results of the residual anomaly map, it shows that the distribution of high anomalies is in the center of the northwest direction and the structural alignment pattern has NESW, NW-SE and almost N-S directions. The results of the Euler Deconvolution method show the presence of structural alignments and rock intrusions with a depth of 10-100 m. The distribution of gold, silver and copper elements is dominant at low magnetic anomaly values and some are at high magnetic anomaly values caused by the presence of diorite intrusion rocks. Based on the modeling results, the subsurface geological model consists of old volcanic rocks with a susceptibility of 0.008-0.102 SI, diorite intrusive rocks at a depth of 20-500 m with a susceptibility of 0.182-0.0257 SI, young volcanic rocks with a susceptibility of 0.015-0.044 SI and alluvial deposits with a susceptibility of 0.014-0.018 SI. Based on the research results, the upward continuation and Euler Deconvolution methods can identify the straightness of the structure, represent the geological conditions and the distribution of mineral elements in the research area well. The results of the RTP process also facilitate the creation of subsurface geological modeling.